Understanding and exploiting the roles of autophagy in plants through multi-omics approaches. (September 2018) - Liu, Fen; Marshall, Richard S.; Li, Faqiang
Highlights: The regulatory mechanism(s) of autophagy was uncovered by transcriptomic studies. Proteomics approaches were used to analyze the dynamics of ATG Proteins. The effects of autophagy on plant development were assessed by metabolomic analyses. Integrative analysis of multi-omics data could provide a precise picture of plant autophagy. Abstract: Autophagy is a highly conserved pathway in eukaryotes that promotes nutrient recycling and cellular homeostasis through the degradation of excess or damaged cytoplasmic constituents. In plants, autophagy is increasingly recognized as a key contributor to development, reproduction, metabolism, leaf senescence, endosperm and grain development, pathogen defense, and tolerance to abiotic and biotic stresses. Characterizing the functional transcriptomic, proteomic, and metabolomic networks relating to autophagy in plants subjected to various extra- and intra-cellular stimuli may help to identify components associated with the pathway. As such, the integration of multi-omics approaches (i.e., transcriptomics, proteomics and metabolomics), along with cellular, genetic and functional analyses, could provide a global perspective regarding the effects of autophagy on plant metabolism, development and stress responses. In this mini-review, recent research progress in plant autophagy is discussed, highlighting the importance of high-throughput omics approaches for defining the underpinning molecular mechanisms of autophagy and understanding its associated regulatory network.